Comparison Of Blood Sorbitol Level And Microalbuminuria In Early Detection Of Diabetic Nephropathy In Type 2 Diabetes - MANJUNATHA GOUD B.K; DEEPA.K; SARSINA DEVI O; POORNIMA A M; NANDINI M; ASHA KAMATH (International Journal of Pharma and Bio Sciences, 2010)
Type 2 DM is a global disease and one of its resultant complication is diabetic nephropathy. An accelerated polyol pathway in diabetes contributes to the development of cataract and nephropathy. Microalbuminuria an early indicator of diabetic nephropathy is an independent risk factor for cardiovascular morbidity and mortality. The main aim of this study was to compare the blood sorbitol levels with microalbuminuria in the early prediction of diabetic nephropathy. The study group included 3 groups of subjects aged between 55-68yrs, Group1-Non diabetic senile cataract patients, Group 2-Diabetic cataract patients without nephropathy, Group3- Diabetic cataract patients with nephropathy. The biochemical parameters estimated included sorbitol, glucose and creatinine in blood; albumin and creatinine in urine. A significant increase in blood sorbitol and glucose along with urine albumin creatinine ratio (UACR) was observed in group 2 and 3. Group 3 showed highly significant increase in blood sorbitol (p<0.01) and UACR (p<0.05) as compared to group 2. Blood sorbitol levels could be used as alternative to MA in the early prediction of diabetic nephropathy.